The Test-Retest Reliability and Minimal Detectable Change of the Sensory Organization Test and Head-Shake Sensory Organization Test - Andrea E. Cripps; Scott C. Livingston; Brandon Desantis (Bowling Green State University, 2016)
Context: The assessment of balance deficits following sport- related concussion can be accomplished using computerized dynamic posturography (CDP) testing procedures, including the Sensory Organization Test (SOT) and the Head- Shake Sensory Organization Test (HS- SOT). Although these tests are considered to be important post- concussion balance assessments, the test- retest reliability of the HS- SOT has not been evaluated in a healthy, athletic population. Objective: Our purpose was to evaluate the test- retest reliability of the HS-SOT in a non-concussed, athletic sample. Design: A prospective, time series, cohort design was used. Setting: University research laboratory. Participants or Other Participants: Twenty (8 F, 12 M) healthy intercollegiate athletes (age 19.95 ± 1.28 years, height 175.55 ± 13.57 cm, weight 74.73 ± 17.59 kg). Interventions: Postural stability was assessed at two time intervals (9 days apart). Subjects completed all 6 testing conditions of the SOT and the 2 testing conditions for the HS- SOT. Results: Excellent test- retest reliability was demonstrated for the SOT composite equilibrium scores (ICC 1,1= .83). Moderate test- retest reliability was observed for the SOT equilibrium scores for conditions 2 (.66) and 5 (.65); somatic (.58), visual (.65), and vestibular sensory analyses (.68); and sensory analysis preference (.66). Moderate reliability was also noted for equilibrium scores on condition 5 for the HS- SOT (.65). The test- retest reliability was poor for the HS- SOT equilibrium scores on condition 2 (ICC= .26, δ2= .14), HS-SOT equilibrium score ratio for fixed surface (ICC= .37, δ2 2= .003). Conclusions: Determining the minimal difference in HS- SOT scores (ICC and MDC) representing significant change over time will help clinicians to identify athletes with balance disorders in the acute post- concussion phase.